Integrasi nilai-nilai universal olahraga ke dalam pendidikan jasmani: kerangka Pengembangan Pemuda Positif (PYD) - Juhrodin, Juhrodin; Munanjat Saputra, Yudha; Ma’mun, Amung; Yudiana, Yunyun (Universitas Nusantara PGRI Kediri, 2023)
The value given to sports to be taken and applied, especially in the physical education process, to support the development of students' adolescent character, this study aims to integrate the universal values of sports into the seven spheres of physical education learning materials to encourage positive adolescent development. The research method used is quantitative, with a quasi-experimental design. The sampling technique uses purposive sampling techniques, with certain considerations from researchers, including students who do not participate in extracurricular sports, with 60 students. The instrument used was a questionnaire of 73 items designed to measure a universal scale of sports scores with validity tests obtained less stable scores = 0.254. Data analysis techniques describe statistical data, normality tests using Shapiro Wilk, homogeneity tests using Leene tests, and hypothesis testing using paired sample t-tests. The result of this study is that the universal values of sport can be well integrated into every physical education lesson in schools. Students can develop social and emotional skills fundamental to success by utilizing these principles in life inside and outside school. Incorporating these values can also help young people cope with the demands of competitiveness and focus on personal growth, not just winning or losing.